A new ABCA3 Gene Mutation Presenting as Early Neonatal Surfactant Deficiency - Mateus de Abreu, Susana (2021)
Interstitial lung disease is a very heterogeneous group of diseases. Dysfunction of surfactant proteins is included in this group and ABCA3 gene mutations are a well-established genetic cause. There is a large spectrum of clinical presentation concerning ABCA3 mutations ranging from neonatal early death to mild forms of ILD in the adult. We present the case of a newborn with non-consanguineous parents which developed early neonatal respiratory distress with persistent dependence of oxygen. The clinical and radiologic findings were compatible with ILD. The disease progressed towards severe respiratory insufficiency and the patient died at the age of three. A variant not yet described in the literature was found in the ABCA3 gene (c.4442C>T), in apparent homozygosity. Parental genetic studies revealed that only the father was a carrier for this variant. Quantitative study of ABCA3 gene in our patient revealed a deletion affecting exon 32 and most probably exon 29. This report describes the clinical manifestation of a new ABCA3 variant causing surfactant deficiency and ILD while also highlighting the importance of considering gene deletions in case of unconfirmed homozygosity.